SUPPLY CHAIN STRATEGY UNLEASH THE POWER OF BUSINESS INTEGRATION TO MAXIMIZE FINANCIAL, SERVICE, AND OPERATIONS PERFORMANCE - Frazelle, Edward H. (McGraw-Hill Education, 2018)
The industry standard in supply chain management -- fully revised and updated to provide today's logistics solutions The proven pillars of success in logistics and supply chain management introduced in the first edition of Supply Chain Strategy now guide the supply chains of many of the world's most successful organizations, including 3M, Abbott, BP, Coca-Cola, Disney, Hallmark, Honda, Mitsubishi, Oxxo-FEMSA, Payless, P&G, Pratt & Whitney, Wal-Mart, Rio Tinto, and many others. This Second Edition features up-to-date case studies showing how those companies and more meet supply chain goals and helps you overcome your own challenges with the latest supply chain innovations, including big-data analytics, supply chain command and control centers, large-scale supply chain optimization, integrated supply chain planning, real-time global supply chain visibility, omni-channel logistics, re-shoring, global-sourcing optimization, cloud-based supply chain management, supply chain finance, global trade management, and fourth-party logistics.